2016
DOI: 10.1021/acsami.6b12458
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Microwave-Assisted Synthesis of Cubic, Three-Dimensional, Highly Porous MOF-205 for Room Temperature CO2 Fixation via Cyclic Carbonate Synthesis

Abstract: A dual-porous, three-dimensional, metal-organic framework [ZnO(2,6-NDC)(BTB)] (MOF-205, BET = 4200 m/g) has been synthesized using microwave power as an alternative energy source for the first time, and its catalytic activity has been exploited for CO-epoxide coupling reactions to produce five-membered cyclic carbonates under solvent-free conditions. Microwave synthesis was performed at different time intervals to reveal the formation of the crystals. Significant conversion of various epoxides was obtained at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(83 citation statements)
references
References 47 publications
2
81
0
Order By: Relevance
“…From structural data and previous studies, a probable synergistic mechanism during the catalysis by the ZnMOF‐1 /TBAB binary system is proposed, which is also relevant in the case of ZnMOF‐2 . The crystal structures of both ZnMOFs revealed N 2 O 4 coordination around the metal center; the carboxylate group chelated to the metal with a long Zn−O distance (Zn−O2=2.412 Å in ZnMOF‐1 and 2.356 Å in ZnMOF‐2 ) is susceptible for initial catalytic reaction.…”
Section: Resultsmentioning
confidence: 99%
“…From structural data and previous studies, a probable synergistic mechanism during the catalysis by the ZnMOF‐1 /TBAB binary system is proposed, which is also relevant in the case of ZnMOF‐2 . The crystal structures of both ZnMOFs revealed N 2 O 4 coordination around the metal center; the carboxylate group chelated to the metal with a long Zn−O distance (Zn−O2=2.412 Å in ZnMOF‐1 and 2.356 Å in ZnMOF‐2 ) is susceptible for initial catalytic reaction.…”
Section: Resultsmentioning
confidence: 99%
“…MOF‐205, with chemical formula Zn 4 O(BTB) 4/3 (NDC) (BTB = benzene‐1,3,5‐benzoate; NDC = naphthalene‐2,6‐dicarboxylate), is a typical porous material with large surface area, free volume, and low density. These characteristics are all beneficial for gas adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…54 Sun et al found that the adsorption affinity between a H 2 molecule with Li-doped heterofullerene C 48 B 12 55 (Li-C 48 B 12 ) is larger than Li-doped fullerene (Li-C 60 ), where each Li atom can bind up to three H 2 molecules leading to a gravimetric uptake of 9 wt%. 56 MOF-205, 57 with chemical formula Zn 4 O(BTB) 4/ 3 (NDC) (BTB = benzene-1,3,5-benzoate; NDC = naphthalene-2,6-dicarboxylate), is a typical porous material with large surface area, free volume, and low density. These characteristics are all beneficial for gas adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…However,alimited number of MOFs are known for efficient conversion of CO 2 under ambient reaction conditions such as atmospheric pressure, low loading of catalyst/co-catalyst, and room temperature. [78][79][80][81][82][83][84][85][86][87][88][89] On the basis of the above discussions and in ac ontinuation of our ongoing research activity, [12,90] we herewith presentt wo MOFs, {[M(CHDC)(L)]·H 2 O} n comprising Zn II (1)o rC d II (2)m etal nodes andb ipyridyl-based Schiff base ligand, 4-pyridyl carboxaldehyde isonicotinoylhydrazone (L)i nc ombination with flexible 1,4-cyclohexanedicarboxylic acid (H 2 CHDC) and their application in the area of heterogeneousc atalysis. Crystals of MOFs 1 and 2 wereh arvested by diffusion of precursor solutions and, alternatively,b oth MOFs can be obtained quantitatively by conventional reflux and mechanochemical reactionw here the metal salts and ligand precursors are ground together manually to produce bulk homogeneousp hase pure material.…”
Section: Introductionmentioning
confidence: 99%